Creating jobs out of the green: The employment effects of the energy transition - Elisabetta Cappa; Francesco Lamperti; Gianluca Pallante (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
A rapid transition towards renewable energy sources is crucial to address climate change and improve local energy independence. However, the acceptability of this transition often faces resistance due to concerns about potential job-losses in the fossil-intensive sectors, while the employment potential of renewable energy technologies remains unclear. In this study, we address this concern by employing a novel and detailed geolocalized dataset of energy power units across four technologies and three decades, to examine theemployment impacts of renewable energy investments in four large European countries. To mitigate for the possible non-random allocation of renewable energy technologies, we leverage the physical potential of each region in relation to renewable energy sources, to isolate its exposure to technology-specific investments. We find that the deployment of renewable energy plants has a positive and long-lasting impact on employment. Our central estimates suggest that 1 MW of new renewable energy installed capacity creates around 40 jobs in 7 years locally, indicating that 1 Million USD invested in renewable energy technologies generates approximately 15 jobs over the same time frame. These estimates are mostly driven by the effects generated by the solar and wind installations on the construction sector. We find evidence of substantial heterogeneities across regional features, where rural and low-income areas are the ones experiencing the largest employment effect from renewable energy deployment. Overall, our findings suggest that green energy investments can constitute as a strategic asset to spur local jobs and encourage rural development.
Keywords: C26; H50; P18; Q20; Q43; Q52; 330; renewable energy; employment multiplier; green stimulus; shift-share